Optimizing examination of methylenetetrahydrofolate reductase gene promoter methylation in cleft lip with or without cleft palate non-syndromic patients using the pyrosequencing method - Maskoen, Ani Melani; Rahayu, Nurul Setia; Nasroen, Saskia Lenggogeni (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Cleft lip with or without cleft palate (CL/P) is the most common congenital anomaly found in Indonesia. CL/P is caused by hereditary (genetic) and environmental factors. Environmental factors can result in methylation in the promoter of the methylenetetrahydrofolate reductase (MTHFR) gene, affecting its expression. Methylation takes place at the CpG site found at chromosome 1, coordinates 11,805,406–11,806,509. Pyrosequencing technology can detect the percentage methylation of a gene quickly, simply, and accurately. Purpose: The aim of the study is to optimize detection of methylation of the MTHFR gene using the pyrosequencing method. Methods: Methods used in this study were DNA extraction from blood, DNA bisulfite conversion, polymerase chain reaction (PCR), and methylation detection using CpG pyrosequencing assay. Samples were taken from 20 CL/P patients (C) and 44 normal patients (N). Results: The pyrosequencing method was successful in detecting methylation at three MTHFR gene sites at coordinates 11,805,507–11,805,529. The methylation level at the third site was higher in group C than in group N, while at the first and second positions, group C had a lower methylation level than group N. In general, the percentage of methylation for both groups was low or hypomethylated (less than 5%). Conclusion: The pyrosequencing method can be used to determine methylation levels in the MTHFR gene with the results presented as percentages (quantitative data). Hypomethylation occurs in groups C and N at the coordinates 11,805,507–11,805,529 of the MTHFR gene promoter.